2022
DOI: 10.1002/cam4.4888
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, risk factors and outcomes of cancer patients withCOVID‐19: A population‐based study

Abstract: Introduction Cancer patients may be susceptible to poorer outcomes in COVID‐19 infection owing to the immunosuppressant effect of chemotherapy/radiotherapy and cancer growth, along with the potential for nosocomial transmission due to frequent hospital admissions. Methods This was a population‐based retrospective cohort study of COVID‐19 patients who presented to Hong Kong public hospitals between 1 January 2020 and 8 December 2020. The primary outcome was a composite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…The present study also showed that the prevalence of chronic respiratory diseases, except for asthma, was significantly higher in cancer patients with COVID-19, which is consistent with a number of previous studies 32 , 24 . On the contrary, some studies reported that there is no significant difference between cancer and non-cancer patients in terms of the prevalence of chronic respiratory diseases 9 , 10 , 12 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study also showed that the prevalence of chronic respiratory diseases, except for asthma, was significantly higher in cancer patients with COVID-19, which is consistent with a number of previous studies 32 , 24 . On the contrary, some studies reported that there is no significant difference between cancer and non-cancer patients in terms of the prevalence of chronic respiratory diseases 9 , 10 , 12 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the rates of ICU admission, intubation and death in cancer patients were significantly higher compared to non-cancer patients. These findings are in line with some previous studies 11 , 16 , 24 showing that cancer patients with COVID-19 were at higher risk for ICU admission, intubation, and death compared to people without malignancy. Patients with malignancy need more attention due to their sensitivity to infections and weak immune system, so under particular circumstances such as an epidemic of a viral disease, they definitely experience weaker outcomes compared to other patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[12] However, few studies have assessed the role of CRP in cancer patients with COVID-19 infection. [13][14][15] Therefore, this cross-sectional study aims to assess the association between serum CRP levels and COVID-19 pneumonia in cancer patients infected with the Omicron variants from December 8, 2022 to February 1, 2023 in China.…”
Section: Introductionmentioning
confidence: 99%